Faktor Faktor Yang Memengaruhi Produktivitas Kelapa Sawit Swadaya Di Desa Lubuk Tajau Kecamatan Nanga Taman Kabupaten Sekadau - Hendi, Hendrikus; Maswadi, Maswadi; Fitrianti, Wanti (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Oil palm is the most important plantation product in Indonesia, helping rural communities' economic well-being. The country's earnings from foreign exchange are 608 trillion dollars thanks to these commodities. In the Lubuk Tajau Village of the Nanga Taman District of the Sekadau Regency, the purpose of this study is to investigate the influencing factors on oil palm productivity. There were 37 independent oil palm smallholders who participated in this study. This study utilized both primary and secondary data. The central statistics agency, palm oil farmers' unions, and other supporting literature served as sources of secondary data, while farmer interviews, observations, and questionnaires provided primary data. Using the Cobb-Douglas production function model and multiple linear regression, the obtained data were analyzed. The consequences of the examination of the elements that essentially affect the efficiency of autonomous oil palm in Lubuk Tajau Town, Nanga Taman Locale, Sekadau Regime are the variables of NPK manure, SP-36 and the age of the respondents. Herbicides, KCL, labor, plant distance, farming experience, and education are among the other factors that have no significant impact